Sum Of 2 Primes

Which of the following numbers could be the sum of 2 prime numbers?

41 39 35 37

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Avner Lim
Mar 10, 2021

Since all of the options have odd numbers as their numbers, and only even + + odd = odd, the only prime number which is even is 2. Now we can try checking each of the options. 41 2 = 39 41 - 2 = 39 , which is incorrect because 39 = 3 × 13 39 = 3 \times 13 , so 39 39 is not a prime number. 39 2 = 37 39 - 2 = 37 , which is correct because 37 37 is a prime number. So the answer is 39 \boxed{39} .

Naren Bhandari
Jul 26, 2018

Short solution

Notice that sum of any two prime numbers is always an even number . Since the sum of two primes is odd . Therefore, one of the prime must be even which is clearly 2. Then S = p + 2 p = S 2 S= p+2 \implies p = S-2 From the given sums we find p = 37 S = 39 p= 37\Rightarrow S = \boxed{39} .


Explained solution

For any prime number ( p > 5 ) \,(p>5) can be expressed as p = 6 k ± 1 c c k N p = 6k \pm 1\phantom{cc} k\in\mathbb N Say two primes ( p 1 , p 2 ) \,(p_1 ,p_2) are greater than 5. Then following above formula (not a general formula )we can have S = p 1 + p 2 = ( 6 k 1 ± 1 ) + ( 6 k 2 ± 1 ) = 2 { 3 ( k 1 + k 2 ) ± 1 } c or c 6 ( k 1 + k 2 ) S = p_1+p_2 = \,(6k_1\pm 1 )+\,(6k_2 \pm 1)= 2\left\{3\,(k_1+k_2)\pm 1\right\}\phantom{c} \text{or} \phantom{c}6(k_1+k_2) Shows that sum of two primes is an even number and among given S S , we have only odd numbers. From here can conclude that one them prime ( p 1 < 5 ) \,(p_1 <5) and p 2 > 5 p_2>5 since maximum S = 41 S=41 .

Obviously, p 1 = 2 p_1=2 and then S = 2 + 6 k 2 ± 1 k 2 = S 2 ± 1 6 = { S 1 6 = 34 6 , 38 6 , 40 6 , 6 S 3 6 = 32 6 , 6 , 38 6 , 34 6 S = 2 + 6k_2\pm 1 \implies k_2 = \dfrac{S-2\pm 1 }{6}= \begin{cases} \dfrac{S-1}{6} = \dfrac{34}{6}, \dfrac{38}{6} , \dfrac{40}{6} , 6\\\dfrac{S-3}{6}=\dfrac{32}{6}, 6 , \dfrac{38}{6} , \dfrac{34}{6}\end{cases} We obtained k 2 = 6 p 2 = 6 × 6 ± 1 = 35 , 37 k_2 =6 \implies p_2 = 6\times 6\pm 1 = 35 , 37 and possible sum we can obtained is S = 37 + 2 = 39 S = 37+2=39 .

That's not what actually happens with ± \pm . For example, we have 7 + 11 = 18 7 + 11 = 18 is a multiple of 3.
There is no reason why if the first sign is a + + , then the second sign is also a + + . In the counter example, we had + , +, - .

Chung Kevin - 2 years, 10 months ago

Log in to reply

However, we can considered the three different cases of + , + , , + , +, - , - and + , +,- . The third case i deliberately left since the sum cannot be obtained with this case.

Naren Bhandari - 2 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...